Nahoum Index in Brachyfacial Patients: A Pilot Study - Chiara Vompi; Roberto Vernucci; Ambra Maria Costantini; Valentina Mazzoli; Gabriella Galluccio; Alessandro Silvestri (Galenos Yayinevi, 2020)
Objective:Our aim is to test the Nahoum Index as a support in the cephalometric study of vertical dimension and therapeutic orientation in adult patients suffering from Class II malocclusion, deep bite, or short face syndrome.Methods:Twenty-three patients with molar Class II and an overbite >4 mm were stratified into two groups: orthodontic (G2) and surgical orthodontic (G1). The ANB angle and Nahoum Index were calculated for cephalometric tracing pre- and post-treatment. The difference between the ANB and Nahoum Index values were analyzed using the Statistical Package for the Social Sciences software.Results:In G1, the Nahoum Index decreased from 0.954 to 0.797, and the ANB angle decreased from 5.2° to 3.2°. In G2, the Nahoum Index decreased from 0.825 to 0.817, and the ANB angle decreased from 4.4° to 4°.Conclusion:In G1, the difference between before and after treatment was significant for the Nahoum Index only. The difference between before and after values was not significant in the G2 group. It is possible to indicate the Nahoum Index of 0.934 as the limit value in case of which a patient may be treated with orthodontics only. This limit is the opposite of the limit proposed by Nahoum for vertical excess cases and respect the same interval. Therefore, we can consider the range 0.81-0.934 to indicate borderline patients, and >0.934 to indicate surgical patients. If the ratio is close to the normal value as 0.81, the treatment will be orthodontic; if it is further increased, the treatment will be surgical.